Metabolic profile and spontaneous physical activity modulation under short-term food restriction in young rats. - Wladimir Rafael Beck; Pedro Paulo Menezes Scariot; Stefânia Santos do Carmo; Fúlvia Barros Manchado-Gobatto; Claudio Alexandre Gobatto (Universidade Estadual Paulista (UNESP), 2017)
Abstract AIMS The aim of this study was to investigate the effects of short-term food restriction (6-weeks) on metabolic profile and spontaneous physical activity (SPA) of young male Wistar rats. METHODS Thirty rats had their baseline SPA measured at 21 days-old and were separated into two groups at 28 days-old: Control (CG) and 50% of food restriction (FR). The food restriction protocol lasted six weeks, being the SPA measured weekly by a gravimetric apparatus. At the end of the experiment, biochemical analyses were performed in serum and tissue samples with statistical significance set at 5%. RESULTS FR showed less SPA than CG, as occurred for body mass, water intake, adipose tissue and liver, heart and soleus glycogen, serum glucose, total protein, triglycerides and total cholesterol (P<0.05). CONCLUSION Data set demonstrates that low substrate stores signaled to decrease spontaneous physical activity to save energy.